P27kip1 overexpression regulates IL-1β in the microenvironment of stem cells and eutopic endometriosis co-cultures. (January 2017) - Gonçalves, G.A.; Invitti, A.L.; Parreira, R.M.; Kopelman, A.; Schor, E.; Girão, M.J.B.C.
Highlights: p27 kip1 gene therapy can decrease the IL-1β production in endometriosis. p27 kip1 gene therapy as an alternative strategy in the treatment of endometriosis. p27 kip1 gene therapy as an regulator of Il-1β in endometriosis. Abstract: Endometriosis is a gynecological benign chronic disease defined as the growth of endometrial glands and stroma in extra-uterine sites, most commonly implanted over visceral and peritoneal surfaces within the female pelvis causing inflammatory lesions. It affects around 10% of the female population and is often accompanied by chronic pelvic pain, adhesion formation and infertility. Therefore, endometriosis could be considered a "social disease", since it affects the quality of life, reproductivity and also has a socio-economic impact. The expression of cell cycle and inflammatory proteins is modified in the endometriotic tissues. Immunostaining of glandular and stromal cells in endometrial biopsies obtained from patients with endometriosis compared with those of healthy control demonstrated that endometriotic tissues have lower levels of p27 kip1 protein. Endometriosis endometrial cells cultures have also lower levels of p27 kip1 compared to health endometrial cells cultures and restore the cell cycle balance when transduced with an adenoviral vector carring the p27 kip1 coding gene (Adp27EGFP). The low levels of p27 kip1 are related to the S phase in the cell cycle, whereas higher levels lead to a G1 cell cycle arrest. The inflammatory cytokine IL-1β was recently identified as another key protein in the endometriosis proliferation. This cytokine has elevated levels during the proliferative and secretory phases of the menstrual cycle. In endometriosis endometrial cells cultures the IL-1β stimulates the production of IL-6 and IL-8, increasing the cell proliferation and reducing the apoptosis and Bax expression in these cells. According to these remarks, this work aims to evaluate the inflammatory effects in vitro, but more next to what happens in a woman's body, associating endometrial cells with stem cells, thus mimicking the endometrial microenvironment, with gene therapy using Adp27, notoriously known as controller cell cycle, apoptosis and potent modulator of VEGF expression.